How Patient Centered Are Addiction Treatment Intake Processes?. Issue 2 (March 2021) - Mark, Tami L.; Hinde, Jesse; Henretty, Kristen; Padwa, Howard; Treiman, Katherine
Abstract : Objectives: The substance use disorder (SUD) treatment field has conducted significant research on creating intake tools and processes that best match patients to the most appropriate treatment setting, but less research has been conducted on how those tools impact the patient experience. The study took advantage of a natural experiment in California to evaluate whether the implementation of American Society of Addiction Medicine (ASAM) assessment criteria and a computer-facilitated intake assessment based on the ASAM criteria affects patient experiences and patient-centeredness during intake relative to patients receiving intake assessments not based on ASAM criteria. Methods: We analyzed surveys completed by 851 patients covered by Medi-Cal who were receiving specialty SUD treatment at 33 providers across 10 California counties about their experiences and perceptions of the intake assessment process. To account for differences in patient mix, we used inverse-probability weighting and computed differences in the weighted means for patients across non-ASAM, ASAM, and computerized-ASAM patients. Results: We have found that patients who underwent intake based on ASAM assessment criteria or computerized ASAM assessment experienced a more patient-centered intake. We also found that patients who received ASAM-based assessments were more satisfied with their choice of treatment setting. Conclusions: This evidence is encouraging for the SUD treatment field, especially considering that many Medicaid programs are adopting ASAM or similar patient placement criteria and multidimensional assessments. Future research should consider whether increases in the patient-centeredness of assessments are associated with increased retention in SUD treatment and other positive treatment outcomes. Abstract : Supplemental Digital Content is available in the text